PERANAN DOKTER RM. PRATOMO SEBAGAI SEORANG PERINTIS KESEHATAN MASYARAKAT BAGANSIAPIAPI 1910-1939 - SETYAWATI, SETYAWATI; isjoni, Prof. Dr. Isjoni, M.Si; ibrahim, bedriatiibrahim@gmail.com (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
ROLE OF RM DOCTORS. PRATOMO AS A PIONEER OF BAGAN SIAPIAPI PUBLIC HEALTH 1910-1939 Setyawati *, Prof. Dr. Isjoni, M.Sc **, Dra. Bedriati Ibrahim, M.Sc *** Email: wsetya570@gmail.com, isjoni@yahoo.com, bedriatiibrahim@gmail.com Cp: 081268303452 Historical Education Study Program Department of Social Sciences Education Faculty of Teacher Training and Education, University of Riau Abstract: Around the 19th century the Hindia Dutch government lacked medical personnel in its colonies namely Indonesia. Starting from a variety of diseases that plagued the population in 1847, with thus attempting to recruit indigenous workers as doctors was cheap and easy to obtain. then a school of Javanese Medical Schools (STOVIA) was established. The purpose of this study is 1) To find out the beginning of the entry of the Netherlands in Bagansiapiapi, 2) To find out the reasons for the doctor's RM. Pratomo came to Bagansiapiapi, 3) To find out the role of Doctor RM. Pratomo as a pioneer of bagan siapi-api public health 1910-1939, 4) To find out the development of the hospital that was built by the Doctor RM. Pratomo 1910-1939. As for this study using qualitative research methods with a historical approach and data collection techniques in the form of observation, direct interviews and documentation. The results of this study were doctor RM. Pratomo was a doctor who was transferred to the Bagansiapiapi area and became the first doctor in Bagansiapiapi. Doctor RM. Pratomo built medical clinics and treated local people to communities in the countryside near the Rokan River. So much the role of the doctor RM. Pratomo as the only doctor in Bagansiapiapi so that we should remember his services and preserve his heritage. Key Words: Role, Health Pioneer